The effect of health, spatial planning and work discipline on employee work effectiveness - Kurbani, Adi; Novalia, Nurkardina; Nuarly, Machmud (Goodwood Publishing, 2023)
Purpose: This study aims to examine the influence of health, spatial layout, and work discipline on employee work effectiveness. Methodology/Approach: An associative quantitative method was employed with a population comprising 50 State Civil Apparatus (ASN) at the Ogan Komering Ilir Regency Education Office. The sampling technique used was purposive non-probability sampling. Data were collected through primary sources, namely questionnaires distributed to respondents, and secondary sources, including documentation and relevant literature studies. Results/Findings: The results of the t-test indicate that health, spatial layout, and work discipline variables each partially influence work effectiveness. Furthermore, the F-test confirms that these three variables collectively exert a positive and significant effect on employee work effectiveness. These findings suggest that the optimization of workplace health, spatial arrangements, and discipline policies directly contributes to improved performance. Conclusion: Employee work effectiveness is significantly shaped by health, spatial layout, and work discipline, both individually and in combination. Strategic improvements in health programs, office spatial design, and discipline reinforcement can substantially enhance overall performance at the Education Office. Limitations: This study is limited to ASN employees within one agency, thereby restricting generalizability to broader populations. Contribution: The study offers insights for human resource development and provides a benchmark for future academic inquiry. It contributes to academic literature, practical evaluation, and policy considerations, particularly for leadership in enhancing health standards, workplace design, and discipline measures to improve employee effectiveness.